Occurrence of metacercariae of Diplostomum and Tylodelphys species (diplostomidae) in Clarias species (clariidae) fishes from Lake Victoria - Musiba, M. J.; Nkwengulila, G. (Tanzania Journal of Science, 2021)
The localisation and abundance of the metacercariae of Diplostomum and Tylodelphys species among the clariids of Lake Victoria were investigated between April and December 2001. Four species viz. Clarias gariepinus (271), C. alluaudi (65), C. werneri (50) and C. liocephalus (47) were examined, but only C. gariepinus was infected in the brain case and along the nasal cavity. Prevalence of metacercariae was high (>70%). Prevalence and mean intensity were similar between male and female fish. Mean intensity increased with fish size and declined in larger fish for D. mashonense; but declined with the increase in fish size for Tylodelphys species. The metacercariae were over-dispersed and the variance to mean ratio curves behaved similarly to mean intensity. Possible factors leading to the observed infection patterns are discussed.